The Effect of Population Growth and Economic Factor to Conversion Function of Agricultural Land Supply Chain in North Aceh District - Wesli, Wesli (International Journal of Supply Chain Management, 2018)
Population growth and economic factors are the causes of changes agricultural land supply chain use in North Aceh District. The regional development requires land for housing, industry, trade and other purposes while land availability was constant, resulting in land conversion from the function of agricultural land supply chain to non-agricultural. The shifting of land use from 2012 to 2015 was significant in the reduced farm forestry 7,138 ha, agricultural estate 6,465 ha and Wetland area of 227 ha. The purpose of this study was to determine the significance of the effect of population growth and economic factors on the conversion of agricultural land supply chain into non-agricultural land supply chain. The method used was Quantitative Method by using Structural Equation Model (SEM). The results showed that population growth and economic factors affect the conversion of land from agricultural land supply chain to non-agricultural land supply chain, especially in urban areas. The shift in the dominant production area for housing, store shops because it is more profitable as a place of business in increasing peoples income but this causes the reduction of agricultural land supply chain as a support food support